The Influence of Organizational Culture, Leadership and Work Discipline on Employee Performance at the Youth and Sports Department of North Sumatra Province - Aulia, Dita; Tupti, Zulaspan (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to examine the influence of organizational culture, leadership and work discipline on employee performance at the Youth and Sports Department of North Sumatra Province . This research uses associative research with a quantitative approach to determine the relationship or influence between one variable and another. Quantitative data is data expressed in the form of numbers. This research was conducted to examine the influence of organizational culture, leadership and work discipline on employee performance and test hypotheses with a sample size of 91 employees at the Youth and Sports Department of North Sumatra Province. The results of this research show that the Organizational Culture Variable (X1) is known to have a Sig value. 0.001 0.05 and calculated t value = 7.345 t table = 1.663. So it can be stated that Organizational Culture has a positive and significant effect on the Employee Performance variable, the Leadership Variable (X2) is known to have a Sig value. 0.013 0.05 and calculated t value = 5.601 t table = 1.663. So it can be stated that Leadership has a positive and significant effect on the Employee Performance variable, the Work Discipline Variable (X3) is known to have a Sig value. 0.000 0.05 and calculated t value = 6.244 t table = 1.663. So it can be stated that Work Discipline has a positive and significant effect on the Employee Performance variable and the Organizational Culture, Leadership and Work Discipline variables. It is known to have a Sig value. 0.000 0.05 and the calculated F value is 7.342. So it can be stated that Organizational Culture, Leadership and Work Discipline have a positive and significant effect on the Employee Performance variable.